Gastrointestinal follicular lymphoma: using primary site as a predictor of survival. (1st October 2016) - Chouhan, Jay; Batra, Sachin; Gupta, Rohan; Guha, Sushovan
Abstract: Gastrointestinal follicular lymphoma (GI‐FL) is a rare extranodal variant of follicular lymphoma (FL) that has been increasingly reported in the literature. An especially indolent course is linked to the disease after a lack of observed patient death in past studies. However, overall survival (OS) and associated prognostic factors remain unclear. A large population‐based database was utilized to identify demographic and clinicopathologic characteristics of GI‐FL, along with survival differences among primary sites. The Surveillance, Epidemiology, and End Results Registry was used to identify GI‐FL cases between the years of 1973 and 2012. Kaplan–Meier curves compared OS differences and Cox proportional hazard models analyzed prognostic factors. Final analysis included 1109 cases. Small intestinal cases, which included those with single‐site and multi‐segment involvement, were most common (63.6%) followed by gastric (18.2%) and colorectal cases (18.2%). Small intestinal GI‐FL presented more frequently with grade I histology, and less often with grade III histology ( P  < 0.001 and P  < 0.001, respectively). Small intestinal cases had better outcomes (5‐year OS = 80.9%, P  < 0.001) compared to cases involving the stomach (5‐year OS = 52.7%) and colorectum (5‐year OS = 71.5%). On multivariate analysis for predictors of mortality, small intestinal involvement predicted for better survival; hazard ratio (HR) 0.66 (95% CI: 0.51–0.85). Advanced age (≥66), grade (grade III), and stage (Ann Arbor Stage III/IV) predicted for mortality with HR 5.46 (95% CI: 3.80–7.84), 1.42 (95% CI: 1.10–1.83), 1.57 (95% CI: 1.15–2.16), respectively. GI‐FL has poorer outcomes than previously suggested. Small intestinal involvement has a better prognosis. A possible biological basis for this will require further investigations in the future. Abstract : Gastrointestinal follicular lymphoma (GI‐FL) has been characterized as a rare extranodal variant of follicular lymphoma with an especially indolent course; however, long‐term outcomes are relatively unknown. Utilizing a large population‐based database, we found cases of GI‐FL to have poorer outcomes than previously suggested. Additionally, small intestinal primary site involvement may serve prognostic significance and predict for longer survival.